Pre‐emptive Constitution‐Making: Authoritarian Constitutionalism and the Military in Myanmar. Issue 2 (8th May 2020) - Crouch, Melissa
Abstract : Constitutions are an important feature of many authoritarian regimes. But what role do they in fact perform in processes of authoritarian regime stabilization and legitimation? Much of the contemporary literature focuses on authoritarian constitutionalism in transitions away from constitutional democracy. This article considers the opposite scenario: pre‐emptive constitution‐making as a mechanism of authoritarian constitutionalism to contain a potential transition toward constitutional democracy. This is illustrated through the case of Myanmar. Since the 1960s, Myanmar has experienced successive periods of direct military rule without a constitution, followed since 2011 by a new constitution. Adding to the comparative literature on constitutions in authoritarian regimes, this article explains how pre‐emptive constitution‐making limits a transition to liberal democracy and contributes to authoritarian‐regime resilience. This article further identifies "military‐state" constitutionalism as a variation of authoritarian constitutionalism in Myanmar. The case of Myanmar offers comparative insights into the ways constitutions are used to contain transitions to constitutional democracy and illustrates the varieties inherent in authoritarian constitutionalism.